Who gets persuaded? The heterogeneity of campaign effects in the Brexit referendum. (December 2022) - Snow, Dan
Abstract: Political contexts affect the degree to which traditional campaign methods like door knocking and leafleting affect referendum outcomes. Campaign methods are most effective when issues are of low salience and political parties provide unified cues to their supporters. In this paper, I draw on Zaller's model of opinion formation to derive some theoretical expectations about the effectiveness of campaign contact in referendum campaigns when the issue is highly salient but the political parties provide mixed cues, arguing that prior voting intention, rather than partisan identity, should affect receptiveness to campaign messages. I test these expectations with regression analysis of British Election Study panel data, using propensity score matching to mitigate selection bias. My results suggest that the effects of campaigning during the Brexit referendum were mostly small, but differed significantly according to an individual's political attention and, contrary to the theoretical expectations, their partisan identity.